Features of bone tissue remodeling in patients with type 2 diabetes mellitus - Daminov, Abdurasul Takhirovich; Djabbarova, Dilora; Abduvohidova, Nafosat; Furkatova, Diyora; Farxodova, Sevinch; Ibragimova, Parvina (Science and Education, 2023)
The article gives information about features of bone tissue remodeling in patients with type 2 diabetes mellitus.